Dynamics of Breakup Distress and Digital Grieving on Social Media: A Systematic Literature Review: Dinamika Kesedihan Pasca Putus Cinta dan Berduka Secara Digital di Media Sosial: Tinjauan Literatur Sistematis - Ghitsna Nadila Farha; Nur Eva; Imanuel Hitipeuw (Psyche 165 Journal, 2026)
The digital era has transformed how individuals experience romantic relationship dissolution, shifting the mourning process into virtual environments. This study aims to systematically review the dynamics of breakup distress and digital mourning expressions on social media platforms. Using a Systematic Literature Review (SLR) method guided by the PRISMA 2020 framework, 126 records were identified, with nine studies published between 2020 and 2024 meeting the inclusion criteria. The findings reveal that social media serves an ambivalent role in the grieving process. While these platforms provide a space for emotional catharsis, identity reconstruction, and communal support, they simultaneously prolong emotional attachment through digital archives and algorithmic reminders. Emerging themes such as digital hauntings, the use of griefbots, and resistance to online mourning practices highlight the complexity of contemporary loss. This study concludes that digital grieving is a non-linear and technologically mediated experience that redefines traditional grief models. These results underscore the necessity for adaptive psychological interventions and enhanced digital literacy to foster healthy relational closure in an increasingly connected world.